Dealing with dilemmas : where business analytics fall short - Buytendijk, Frank (Wiley, 2010)
Observing how business management is obsessed with analysis and numbers, Dealing with Dilemmas shows there is an entire class of problems that cannot be solved by analysis: business dilemmas. Dilemmas, representing a large part of strategic decision-making, require the opposite approach of analysis; synthesis. Dealing with Dilemmas shows how popular performance management methodologies can be used in new and previously unexplored ways. It authoritatively shows you how your business can move forward strategically in ways previously impossible.: Shows dangers in current thinking around analytics.